2017
DOI: 10.1016/j.expneurol.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle conditioning exercise and diaphragm gene therapy in Pompe disease: Clinical evidence of respiratory plasticity

Abstract: Pompe disease is an inherited disorder due to a mutation in the gene that encodes acid α-glucosidase (GAA). Children with infantile-onset Pompe disease develop progressive hypotonic weakness and cardiopulmonary insufficiency that may eventually require mechanical ventilation (MV). Our team conducted a first in human trial of diaphragmatic gene therapy (AAV1-CMV-GAA) to treat respiratory neural dysfunction in infantile-onset Pompe. Subjects (aged 2-15 years, full-time MV: n=5, partial/no MV: n=4) underwent a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
0
32
1
1
Order By: Relevance
“…Improvements in viral vector delivery and subsequent application of DREADDs may hold a significant therapeutic potential (Saloman et al ., ; Whissell et al ., ) for individuals with peripheral nerve injury. Although many more studies need to be conducted before the clinical use of viral vectors (Castle et al ., ) and designer receptors, the use of gene therapy to treat individuals is not beyond the realm of possibility (Smith et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Improvements in viral vector delivery and subsequent application of DREADDs may hold a significant therapeutic potential (Saloman et al ., ; Whissell et al ., ) for individuals with peripheral nerve injury. Although many more studies need to be conducted before the clinical use of viral vectors (Castle et al ., ) and designer receptors, the use of gene therapy to treat individuals is not beyond the realm of possibility (Smith et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Based on these preclinical studies, the first-in-human trial of diaphragmatic gene therapy (AAV1-CMV-GAA) was conducted in five children with IOPD who required assisted ventilation prior to the study. This trial has been recently completed [145][146][147][148]. The study demonstrated the safety of the AAV treatment, but the clinical outcome was minimal: no improvements in muscle function or dissemination of the GAA transgene were detected outside of the injected tissue.…”
Section: Gene Therapy Strategiesmentioning
confidence: 97%
“…A clinical trial of GAA gene transfer using AAV1 injected into the diaphragm of patients with Pompe disease has recently been completed (20, 21). The study demonstrated the safety of the approach, although the local delivery limited efficacy to the treated diaphragm muscle (20, 21). Another clinical trial is planned (ClinicalTrials.gov ID: NCT02240407) in which an AAV9 vector, carrying the GAA transgene, will be injected intramuscularly in the tibialis anterior of Pompe patients under immunosuppressive regimen (22).…”
Section: Introductionmentioning
confidence: 99%